EVALUATION OF EDENTULISM, INFLUENCE OF SOCIO-ECONOMIC, BEHAVIOURAL FACTORS AND GENERAL HEALTH ON PROSTHETIC STATUS OF ADULT POPULATION OF GEORGIA - Makhviladze, Galaktion; Tsitaishvili, Lela; Margvelashvili, Vladimer; Kalandadze, Manana (European Scientific Journal, ESJ, 2016)
Background: Georgia is a country with a Human Development Index (HDI) score of 0.744. There has not been an epidemiological survey evaluating the edentulism and prosthetic status among the adult population of Georgia since the 1990s. The aim of the study was to identify the level of edentulism from different age and gender groups of the adult population of Georgia, to assess the influence of family income, education level, and general health on people’s prosthodontics status. Methods:The cluster- stratified method with multistage sampling design was used for sampling. Investigated population included 2370 adults-1289 women and 1081 men from nine regions of Georgia and the capital, Tbilisi, distributed in four age groups I- (20-34), II-(35-44), III-(45-64), IV- (65-74). Results: Partial (13.2%) and complete dentures (20.4%) were prevalent in elders, while implant retained prosthesis were observed in only 0.1% of the investigated population. Fixed prosthesis were more noticed in younger population due to partial edentulism. Metal-ceramic (12.4%) and metal crowns (6.3%) were more commonly detected than zirconia ceramic crowns (0.1%). Tooth loss and prosthetic status of the population as well as crown choice was significantly associated with socio-economic, medical (general heath) and behavioral factors. Conclusion: Edentulism is a serious public problem in Georgia. Inadequate Dental prosthetic care, less access to high quality zirconia ceramic crowns and implant retained prosthetic appliances indicates less access to expensive dental procedures in Georgia and is related to low socio-economic, medical and behavioral factors.